Customers’ marketing mix factors and Behavior affect china Guangxi customers to purchase fruit that’s from Thailand in nanning city Guangxi Zhuang Autonomous Region of China - Shen, Zhang; Kaiboriboon, Sorat; Makkanjanakul, Pairat (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The objectives of this research were to: 1) study customers’ marketing mix factors ffect China Guangxi customers to purchase fruit that’s from Thailand in Nanning city Guangxi zhuang autonomous region of China. 2) Compare the marketing mix factors affect China Guangxi customers to purchase fruit that’s from Thailand in Nanning city Guangxi zhuang autonomous region of China through their personal factors. 3) study purchasing behaviours of the customers to purchase fruit that’s from Thailand in Nanning city Guangxi zhuang autonomous region of China and 4) study the correlating purchasing behaviours of the customers to purchase fruit that’s from Thailand in Nanning city Guangxi zhuang autonomous region of China and the personal factors There were 400 samples who are the customers to purchase fruit that’s from Thailand in Nanning city Guangxi zhuang autonomous region of China and the research instrument was a questionnaire. The data were analysis by percentage, mean, standard deviation, t-test and one-way analysis of variance. The results indicated that: 1) Customers’ marketing mix factors affect china Guangxi customers to purchase fruit that’s from Thailand in Nanning city Guangxi Zhuang autonomous region of China, was at a moderate level. Moreover, when each aspect was individually considered, breakdown into Ps, products the distribution, promotion and price. 2) For the customers in Nanning city, differences between sex, age, and monthly average income haven’t affected the decision making for customers in Nanning city. Whereas differences between education level and career have affected the decision making for customers in Nanning at the .05 level with statistical significance 3) The behavior of most of the customers who purchase fruit that’s from Thailand in Nanning city Guangxi Zhuang autonomous region of China, purchase fruit Thai for share with family Members and friends, and interest in the Thai fruit flavor. In the opportunity to purchase, the most of the customers who have the message that’s from friends or relatives, and purchase the Thai fruit at the weekend or Chinese festival in Nanning, and they’ll come back to buy again. And most of the Nanning customers purchase the Thai fruit three to five times per year at night in the shopping malls. However, most of the Nanning customers come to purchase the Thai fruit oneself, and come to buy 1.1 - 2 kg each time about 20.1-40 yuan, but less than 100 yuan per year. 4) The customers in Nanning have the personal factors including sex, age, educationlevel, career, and monthly average income are related to the behavior of the Nanningcustomers, this means that the sex, age, education level, career, and monthly average income of the Nanning customers are related to the Nanning customers who purchase the Thai fruit. Article history : Accepted 26 January 2016 SIMILARITY INDEX = 0.00